2008
DOI: 10.1111/j.1471-4159.2008.05763.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Presenilin‐1 and TRAF6 modulates regulated intramembrane proteolysis of the p75NTR neurotrophin receptor

Abstract: The p75 neurotrophin receptor (p75 NTR ) is a member of the tumour necrosis factor superfamily, which relies on the recruitment of cytosolic protein partners including the tumour necrosis factor receptor-associated factor 6 (TRAF6) E3 ubiquitin ligase to produce cellular responses. Recently, p75 NTR was also shown to undergo presenilin-dependent, csecretase-mediated regulated intramembrane proteolysis. In this study, we report the characterization of a highly conserved TRAF6-binding site (PxExxAr/Ac) in presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 83 publications
(116 reference statements)
3
17
0
Order By: Relevance
“…CGNs displayed higher levels of fully processed ICD than HCNs, and this correlated with higher levels of both full-length and proteolytically activated PS-1. In a previous study, NGF-mediated degradation of IkB was found to be compromised in mouse embryo fibroblasts (MEFs) derived from PS-1-knockout mice (Powell et al, 2009), which is in agreement with our DAPT and csec mut results in CGNs. In fact, pharmacological or genetic blockade of p75 NTR cleavage by csecretase in these cells phenocopied the functional profile of HCNs, suggesting that differences in proteolytic processing of p75 NTR might, in part, underlie the divergent signaling activities of this receptor in the two neuronal types.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…CGNs displayed higher levels of fully processed ICD than HCNs, and this correlated with higher levels of both full-length and proteolytically activated PS-1. In a previous study, NGF-mediated degradation of IkB was found to be compromised in mouse embryo fibroblasts (MEFs) derived from PS-1-knockout mice (Powell et al, 2009), which is in agreement with our DAPT and csec mut results in CGNs. In fact, pharmacological or genetic blockade of p75 NTR cleavage by csecretase in these cells phenocopied the functional profile of HCNs, suggesting that differences in proteolytic processing of p75 NTR might, in part, underlie the divergent signaling activities of this receptor in the two neuronal types.…”
Section: Discussionsupporting
confidence: 75%
“…In our own experiments, we have not been able to detect significant changes in the proteolytic cleavage of p75 NTR in either HCNs or CGNs following NGF treatment (data not shown). Other studies have indicated that several other stimuli can influence the proteolytic processing of p75 NTR , including interaction with sortilin , ubiquitylation and palmitoylation (Powell et al, 2009;, activation of Trk receptors (Ceni et al, 2010;Kanning et al, 2003;Urra et al, 2007), myelin-derived ligands (Domeniconi et al, 2005), b-amyloid peptide (Sotthibundhu et al, 2008) and oxidative stress (Kraemer et al, 2014;Le Moan et al, 2011). Aside from its regulation, most studies are in agreement that proteolytic cleavage can affect p75 NTR -mediated signaling and biological activities.…”
Section: Discussionsupporting
confidence: 50%
“…Through genetic knock-out of the presenilins, we have further demonstrated the essential role of the presenilins in ␥-secretase cleavage of TNFR1. Although it has been shown that ␥-secretase cleavage of the insulin-like growth factor 1 receptor, Notch, IL-1 receptor I, p75 NTR , or ErbB-4 receptor occurs in the presence of their corresponding ligands (40,50,58,(77)(78)(79), ligand-induced cleavage has not been shown for other receptors, such as the growth hormone receptor. Here we demonstrate that TNF␣ stimulation can induce ectodomain shedding, generation of TNFR1 CTF, and subsequent ␥-secretase cleavage of TNFR1, perhaps pointing to a general mechanism of ligand-mediated regulated intramembrane proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the TNFR superfamily member p75 neurotrophin receptor (p75 NTR ) undergoes regulated intramembrane proteolysis (55)(56)(57)(58) and that TNFR1 fits the profile of a ␥-secretase substrate, we screened a number of TNF superfamily members to detect involvement of the ␥-secretase protease in their proteolysis and signaling. Using pharmacological inhibitors and genetic knock-out approaches, in this study, we report the identification of TNFR1 as a ␥-secretase substrate and demonstrate that loss of presenilin expression and ␥-secretase activity antagonized TNF-mediated JNK MAPK activation, reduced pro-apoptotic complex II assembly, and inhibited TNF-induced caspase activation and apoptosis.…”
mentioning
confidence: 99%
“…They include SC-1 (36), RhoA (37), and TRAF6 (38,39). In addition, several p75-interacting proteins, such as NRIF (neurotrophin receptor-interacting factor) (21), NADE (p75NTR-associated cell death executor) (40), and NRAGE (neurotrophin receptor-interacting MAGE homolog) (41), contribute to apoptosis in immortalized cell lines.…”
Section: Resultsmentioning
confidence: 99%